Management of post-operative pancreatic fistulas following Longmire–Traverso pylorus-preserving pancreatoduodenectomy by endoscopic vacuum-assisted closure therapy - Dominik J. Kaczmarek; Dominik J. Heling; Maria A. Gonzalez-Carmona; Christian P. Strassburg; Vittorio Branchi; Hanno Matthaei; Jörg Kalff; Steffen Manekeller; Tim R. Glowka; Tobias J. Weismüller (BMC Gastroenterology, 2021)
Abstract Background Pylorus-preserving pancreatoduodenectomy (PPPD) with pancreatogastrostomy is a standard surgical procedure for pancreatic head tumors, duodenal tumors and distal cholangiocarcinomas. Post-operative pancreatic fistulas (POPF) are a major complication causing relevant morbidity and mortality. Endoscopic vacuum therapy (EVT) has become a widely used method for the treatment of intestinal perforations and leakages. Here we report on a pilot single center series of 8 POPF cases specifically caused by dehiscences of the pancreatogastric anastomosis (PGD), successfully managed by EVT. Methods We included all patients with PGD after PPPD, who were treated with EVT between 07/2017 and 08/2020. For EVT a vacuum drainage film (EVT film) or open-pore polyurethane foam sponge (EVT sponge) was fixed to a 14Fr or 16Fr suction catheter and placed endoscopically within the PGD for intracavitary EVT with continuous suction between − 100 and − 150 mmHg. The EVT film/sponge was exchanged twice per week. EVT was discontinued when the PGD was sufficiently healed. Results PGD closure was achieved in 7 of 8 patients after a mean EVT time of 16 days (range 8–38) and 3 EVT film/sponge exchanges (range 1–9). One patient died on day 18 after PPPD from acute hemorrhagic shock, unlikely related to EVT, before effectiveness of EVT could be fully achieved. There were no adverse events directly attributable to EVT. Conclusions EVT could be an effective and safe addition to our therapeutic armamentarium in the management of POPF with PGD. Unless prospective comparative studies are available, EVT as minimally invasive therapeutic alternative should be considered individually by an interdisciplinary team involving endoscopists, surgeons and radiologists.